Its beautiful, if you know the secret

Calculus Level 5

0 π k = 0 sin ( x ( 2 k + 1 ) ) 2 k + 1 d x = π a b , \int _{ 0 }^{ \pi }{ \sum _{ k=0 }^{ \infty }{ \frac { \sin { \left( x\left( 2k+1 \right) \right) } }{ 2k+1 } } } dx= \frac{ \pi ^a } { b },

where a a and b b are integers. Find 10 a + b 10a+b .


Try my Other Problems


The answer is 24.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Humberto Bento
Dec 18, 2014

Set a=2k+1 (a becomes and odd number). And change the integral with the sumation: k = 1 0 π sin ( a x ) a d x = k = 1 [ cos ( a x ) a 2 ] 0 π = k = 1 2 a 2 = 2 k = 1 1 ( 2 k + 1 ) 2 \sum\limits_{k=1}^{\infty }{\int_{0}^{\pi }{\frac{\sin (ax)}{a}dx}}={{\sum\limits_{k=1}^{\infty }{{{\left[ -\frac{\cos (ax)}{{{a}^{2}}} \right]}_{0}}}}^{\pi }}=\sum\limits_{k=1}^{\infty }{\frac{2}{{{a}^{2}}}}=2\sum\limits_{k=1}^{\infty }{\frac{1}{{{(2k+1)}^{2}}}}

Knowing that: k = 1 1 k 2 = π 2 6 \sum\limits_{k=1}^{\infty }{\frac{1}{{{k}^{2}}}}=\frac{{{\pi }^{2}}}{6} The sum of the inverse square off even integers is easy to calculate: k = 1 1 ( 2 k ) 2 = 1 4 k = 1 1 k 2 = 1 4 π 2 6 = π 2 24 \sum\limits_{k=1}^{\infty }{\frac{1}{{{(2k)}^{2}}}}=\frac{1}{4}\sum\limits_{k=1}^{\infty }{\frac{1}{{{k}^{2}}}}=\frac{1}{4}\frac{{{\pi }^{2}}}{6}=\frac{{{\pi }^{2}}}{24} and: k = 1 1 ( 2 k + 1 ) 2 = k = 1 1 k 2 k = 1 1 ( 2 k ) 2 = π 2 6 π 2 24 = π 2 8 \sum\limits_{k=1}^{\infty }{\frac{1}{{{(2k+1)}^{2}}}}=\sum\limits_{k=1}^{\infty }{\frac{1}{{{k}^{2}}}}-\sum\limits_{k=1}^{\infty }{\frac{1}{{{(2k)}^{2}}}}=\frac{{{\pi }^{2}}}{6}-\frac{{{\pi }^{2}}}{24}=\frac{{{\pi }^{2}}}{8}

Therefore the result is: π 2 4 \frac{{{\pi }^{2}}}{4}

and 10a+b = 24

Can you justify the exchange of summation and integral in the first step?

Abhishek Sinha - 6 years, 5 months ago

Log in to reply

Fubini theorem justifies that

Oussama Boussif - 6 years, 5 months ago

They are both sums. Therefore intrrchangeable. You may demostrate that using Riemans sums.

Humberto Bento - 6 years, 5 months ago

Log in to reply

Not really!

Abhishek Sinha - 6 years, 5 months ago

Log in to reply

@Abhishek Sinha You know that both the integral and integral and sum converge - the sun is known to converge (see http://math.stackexchange.com/questions/13490/proving-that-the-sequence-f-nx-sum-limits-k-1n-frac-sinkxk-is), and the integral does too since it has finite limits and is finite at all points between 0 and pi. Then you can freely interchange the summation and integral, since the integral of f(x) + g(x) is the integral of f(x) plus the integral of g(x)

Tanay Wakhare - 6 years, 5 months ago

afaik, you can interchange the sum and integral if the sum is uniformly convergent

Robertson Esperanza - 6 years, 5 months ago

Exactly as me!

Figel Ilham - 6 years, 5 months ago
Incredible Mind
Dec 18, 2014

u can do this without interchanging sum and integral

Yes. You can just integrate term by term to get the same series as above.

Omkar Kamat - 6 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...